2016
DOI: 10.1126/science.aad5227
|View full text |Cite
|
Sign up to set email alerts
|

Rationally engineered Cas9 nucleases with improved specificity

Abstract: The RNA-guided endonuclease Cas9 is a versatile genome editing tool with a broad range of applications from therapeutics to functional annotation of genes. Cas9 creates double-strand breaks (DSBs) at targeted genomic loci complementary to a short RNA guide. However, Cas9 can cleave off-target sites that are not fully complementary to the guide, which poses a major challenge for genome editing. Here, we use structure-guided protein engineering to improve the specificity of Streptococcus pyogenes Cas9 (SpCas9). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
1,860
4
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,072 publications
(1,982 citation statements)
references
References 21 publications
33
1,860
4
15
Order By: Relevance
“…However, when SpCas9-HF1 HNH was bound to a substrate with a single mismatch at the PAM-distal end (20-20 bp mm), stable docking of the HNH nuclease was entirely ablated (Figure 1e). In addition, eSpCas9(1.1) HNH and other high fidelity variants 8,9 reduced the HNH active state in the presence of mismatches (Figure 1f, Extended Data Figure 2c–d). We therefore propose that high fidelity variants of Cas9 reduce off-target cleavage by raising the threshold for HNH conformational activation when bound to DNA substrates.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…However, when SpCas9-HF1 HNH was bound to a substrate with a single mismatch at the PAM-distal end (20-20 bp mm), stable docking of the HNH nuclease was entirely ablated (Figure 1e). In addition, eSpCas9(1.1) HNH and other high fidelity variants 8,9 reduced the HNH active state in the presence of mismatches (Figure 1f, Extended Data Figure 2c–d). We therefore propose that high fidelity variants of Cas9 reduce off-target cleavage by raising the threshold for HNH conformational activation when bound to DNA substrates.…”
mentioning
confidence: 98%
“…Efforts to minimize off-target cleavage by CRISPR-Cas9 have motivated the development of SpCas9-HF1 and eSpCas9(1.1) variants that contain amino acid substitutions predicted to weaken the energetics of target site recognition and cleavage 8,9 (Figure 1a). Biochemically, we found that these Cas9 variants cleaved the on-target DNA with rates similar to that of wild-type (WT) SpCas9, whereas their cleavage activity was significantly reduced on substrates bearing mismatches (Extended Data Figures 1a, 2a).…”
mentioning
confidence: 99%
“…We note that rapid strides are being made to reduce the off-target effects of CRISPR/Cas9. 24,25 In summary, there remains no agreement as to which specific platforms, methods, and interpretations of benefits and risks will need to be applied in the validation of the safety of genome-editing therapeutic applications. Nevertheless, when considered in the context of somatic therapy, novel methods of genome editing such as CRISPR/Cas9 will probably raise few truly novel ethical issues that have not been addressed in previous contexts, such as with gene-therapy trials.…”
Section: Introductionmentioning
confidence: 99%
“…However, off target Cas9 activities in the plant genome have been detected only rarely [5]. Moreover, recent work has identified Cas9 enzymes that give fewer off-target effects, thus further reducing this concern in plants [138]. Harnessing the CRISPR/Cas9 machinery to engineer plant resistance to viral pathogens also opens the possibility of addressing basic questions in virus infection and plant host resistance.…”
Section: Molecular Based Approachesmentioning
confidence: 99%